Balancing Objectives: An Integrated Approach with Goal Programming and Intellectual Property Rights in Decision-Making (International Journal of Scientific Research in Science and Technology, 2025)
Contemporary organizational decision-making necessitates reconciling conflicting strategic objectives while navigating complex intellectual property (IP) landscapes. This study proposes a novel integrated framework that synergizes Goal Programming (GP) optimization techniques with Intellectual Property Rights (IPR) considerations to facilitate balanced, legally robust decisions. Traditional multi-objective models often overlook the legal and strategic implications of IPR, risking suboptimal innovation outcomes and competitive vulnerability. Our approach operationalizes IP constraints—such as patent protection, licensing terms, infringement risks, and exclusivity windows—as explicit goals or system boundaries within a GP formulation. Through a case study in Specify Sector pharmaceutical R&D or technology commercialization, we demonstrate how lexicographic/preemptive GP prioritizes critical IP-driven goals freedom-to-operate, IP cost minimization alongside operational targets cost efficiency, time-to-market. Results confirm that the framework significantly enhances decision transparency, mitigates IP-related risks, and aligns innovation investments with organizational strategy. This research contributes to operations management and innovation policy by providing a quantitative methodology for harmonizing economic objectives with IP imperatives, offering practitioners a actionable tool for strategic resource allocation in IP-sensitive environments.